Structural Characterization of a Low Molecular Weight HG-Type Pectin From Gougunao Green Tea - Hong, Tao; Zhao, Jiaying; Yin, Junyi; Nie, Shaoping; Xie, Mingyong (Frontiers in Nutrition, 2022)
Tea is a popular beverage with a long history of safe and healthy use. Tea polysaccharide is a bioactive component extracted from tea, which has attracted more and more attention in recent decades. In this article, an acidic polysaccharide Gougunao tea polysaccharide (GPS) was isolated from Gougunao green tea by hot water extraction and ethanol precipitation. After purification by a diethylaminoethyl (DEAE) Sepharose Fast Flow column and a Sephacryl S-400 column, several homogalacturonan (HG) and rhamnogalacturonan-I (RG-I) fractions were obtained. Fraction GPS2b with the highest yield was selected for structural characterization by methylation and nuclear magnetic resonance (NMR) analysis. GPS2b was found to be an HG-type pectic polysaccharide (degree of methyl esterification [DE], 51.6%) with low molecular weight (Mw, 36.8 kDa). It was mainly composed of →4)-α-GalpA- (1→ and →4)-α-GalpA-6-OMe-(1→. In addition, a minor highly branched RG-I domain was identified in this fraction. The investigation of structural features of tea polysaccharides can provide insights to understand their structure-bioactivity relationship.